Investigation of Intolerance of Uncertainty and Defensive Pessimism Levels of Sports Workers in the Pandemic Process with Different VariablesAbstract - DEMİR, Mustafa and KILIÇKAYA, Okan and SERİN YAMAN, Sevinç (International Journal of Holistic Health, Sports and Recreation, 2023)
The aim of this study; To examine the level of intolerance to uncertainty of sports workers who try to live under financial and moral uncertain conditions as a result of the suspension and cancellation of sports services, organizations and competitions under the conditions of the Covid-19 pandemic, In the study, the relational screening and causal comparison model, which is one of the general screening models was used, and for the sample group; there are 379 sports workers (trainers and athletes) working in sports clubs and facilities in Istanbul. Intolerance to Uncertainty Scale and Defensive Pessimism Scale were used as data collection tools. Tthere was no significant difference in the level of Intolerance of Uncertainty according to the age variable of the participants, a significant difference was found in the levels of defensive pessimism. According to the variable of educational status, there were differences between the groups in both scales. It was determined that the variable of the economic level of the participants did not affect the sense of intolerance to uncertainty, but increased the level of defensive pessimism. In the correlation analysis examining the effects of both scales on each other, a positive relationship was found between intolerance to uncertainty and defensive pessimism levels. As a result, there is a positive relationship between the level of intolerance of uncertainty and defensive pessimism of sports workers. For this reason, it is important to create suitable conditions for sports workers to continue their careers successfully and not to worry about the future.